Modelo explicativo de la influencia de la diversidad sobre el desempe\~no de los grupos de trabajo: El efecto moderador de la dirección estratégica de los recursos humanos - Fernando Martín Alcázar; Pedro Miguel Romero Fernández; Gonzalo Sánchez Gardey (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2006)
The transformation of actual societies draws organizations characterised more than ever by diverse workforces. Under this new circumstance, strategic human resource management models must be reconsidered, to break the classic assumption that employees constitute a generic and homogeneous category. In this sense, this paper defines diversity as a multidimensional construct, and analyse its effects on organizations, through the introduction of group dynamics as a variable that mediates the relationship between diversity and performance. Drawing on this explanation, this paper explores the role played by strategic human resource management in this process, applying the classical configurational model that distinguishes between control and commitment human resource patterns. From this analysis, we conclude that the strategic human resource system moderates the diversity-performance relationship. Therefore, positive or negative effect of diversity will depend on how human resource strategy, policies and practices are developed.
Keywords: 330; diversity; strategic human resource management; human resource patterns; theoretical model